UPAYA PERTAHANAN KEBERLANGSUNGAN INDUSTRI KERAJINAN ONIX DAN MARMER KABUPATEN TULUNGAGUNG - Wahyu Rizki Aris Suseno (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2021)
The writing of this article aims to provide an analysis of the efforts made by Onix and marble handicraft businesses in maintaining the sustainability of their industries including product development, market development, financial management, and family economic education. The writing of this research used a qualitative approach as well as a phenomenological research method. The subject is the handicraft and marble business actors in the Campurdarat District. The technique used is data collection techniques in the form of observation, documentation, interviews, and triangulation. This research obtained the results, namely: (1) product development used, namely by modifying existing products (2) Market development is carried out by marketing products that have been produced not only through offline but also online, such as social media and market places. (3) financial management, some industrial owners have planned well on finances. (4) Industry owners also apply for family economic education in an effort to maintain the companies they have founded.